ИЗУЧЕНИЕ БЕЛКОВОГО СОСТАВА СЫВОРОТКИ КРОВИ МАРАЛОВ – РОГАЧЕЙ (Experimental biology, 2009)
Albumen fractions of blood serum of stag marals were determined by photometric method. Changeability of Albumen fractions of blood serum of stag marals was determined based on the age. Duringtheir growth increasing of globulin’s concentration in the blood indicates intensity of turnover and functional activity of tissues. Increase of additional weight of stag marals directly depends on balanced feeding andcontent of crude protein and globulin. As globulin fractions in the blood decreases so far daily weight gain decreases. Researches detected that increase of crude protein in the blood is caused by increase of β’s and γ-globulin’s amounts, and their complex with lipids.
Keywords: marals